Hubungan Minat dan Motivasi dengan Hasil Belajar Teknik Instalasi Penerangan Listrik Siswa SMKN 2 Tanimbar Selatan - Sermatan, Silfina; Sangi, Nontje; Sanger, Ruddy (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2021)
This study aims to: 1 analyze the relationship between interest and learning outcomes of Electrical Lighting Installation Engineering students at SMK N 2 Tanimbar Selatan; 2 analyze the relationship between motivation and learning outcomes of Electrical Lighting Installation Engineering students at SMK N 2 Tanimbar Selatan; 3 analyze the relationship between interest and motivation together with learning outcomes of Electrical Lighting Installation Engineering students at SMK N 2 Tanimbar Selatan This study uses a quantitative correlational method approach to obtain a systematic factual and accurate design by describing the relationships between the independent or independent variables X1 X2 and the dependent or dependent variable Y as well as how big the level of correlation between the variables is based on the correlation coefficient Based on research on the relationship of interest and motivation with learning outcomes of Electrical Lighting Installation Engineering students of SMK N 2 Tanimbar Selatan it is obtained that the level of the relationship between interest and learning outcomes motivation and learning outcomes as well as the relationship between interest and motivation together with learning outcomes has a high level of correlation < p> Abstrak Penelitian ini bertujuan untuk: 1 menganalisis hubungan minat dengan hasil belajar Teknik Instalasi Penerangan Listrik siswa SMK N 2 Tanimbar Selatan; 2 menganalisis hubungan motivasi dengan hasil belajar Teknik Instalasi Penerangan Listrik siswa SMK N 2 Tanimbar Selatan; 3 menganalisis hubungan minat dan motivasi secara bersama sama dengan hasil belajar Teknik Instalasi Penerangan Listrik siswa SMK N 2 Tanimbar Selatan Dalam penelitian ini menggunakan pendekatan metode kuantitatif korelasional yang bertujuan untuk mendapatkan rancangan secara sistematis faktual dan akurat Dengan mendeskripsikan hubungan hubungan antara variabel indepeden atau bebas X1 X2 dan variabel dependen atau terikat Y serta seberapa besar tingkat korelasi antara variabel variabel berdasarkan koefisien korelasi Berdasarkan penelitian tentang hubungan minat dan motivasi dengan hasil belajar Teknik Instalasi Penerangan Listrik siswa SMK N 2 Tanimbar Selatan diperoleh tingkat hubungan minat dengan hasil belajar motivasi dengan hasil belajar serta hubungan minat dan motivasi secara bersama sama dengan hasil belajar yaitu mempunyai tingkat korelasi yang kuat < p>